KEPUASAN KLIEN DAN KEGUNAAN LAPORAN AUDIT EKSTERNAL STAKE HOLDER (PERSPEKTIF KLIEN AUDIT) - Tubagus Ismail (LPPM Universitas Terbuka, 2015)
The purpose of the paper is to test a structural equation model (SEM) of client satisfaction with the audit, and of client perception of the usefulness of the audit to external stakeholders. A questionnaire was mailed to audit clients, i.e. of manufacturing go public companies in the province of Banten; 57 useable questionnaires were returned. Data were processed using the SEM software Partial Least Square (PLS). The data suggest that auditors face difficulties in handling divided loyalties, as audit clients perceive a strong relationship between client satisfaction and usefulness to external stakeholders. The higher auditors competence is perceived to be by the clients, the more satisfied they are with the audit and the more useful they believe the audit is to external stakeholders. The more skeptical the auditor is perceived to be by the clients, the less satisfied they are with the audit and the moreuseful they believe the audit is to external stakeholders. The findings extend previous results, the better the relationship with the auditor is perceived to be by the clients, the more satisfied they are with the audit and the less useful they believe the audit is to external stakeholders. The study addresses an issue most auditing research has not explicitly considered: the distinction between client satisfaction with the audit and client perceptions of the usefulness of the audit to external stakeholders. Tujuan dari artikel ini adalah untuk menguji model persamaan struktural (SEM) atas kepuasan klien, audit, dan persepsi klien tentang kegunaan audit kepada pemangku kepentingan eksternal. Responden penelititan ini adalah 57 klien audit, yang bekerja di perusahaan manufaktur go public di Provinsi Banten. Data diolah dengan menggunakan softwareSEM Partial Least Square (PLS). Hasil penelitian menunjukkan bahwa auditor menghadapi kesulitan dalam menangani kesetiaan yang terbagi bagi, antara harus berada pada posisi kepuasan klien dan kegunaan kepada para pemangku kepentingan eksternal. Semakin berkompeten auditor, semakin puas klien audit dan lebih bermanfaat untuk stakeholdereksternal. Semakin skeptis auditor yang dianggap oleh klien, semakin kurang puas mereka klien audit dan semakin berguna untuk stakeholdereksternal. Semakin baik hubungan dengan auditor yang dianggap oleh klien, semakin puas klien audit dan kurang berguna bagi stakeholdereksternal. Penelitian ini membahas masalah penelitian audit belum secara eksplisit dipertimbangkan.